Night lunch - Fan, Eric (Tundra Books, 2022)
"A mysterious cook whips up midnight meals for fellow night owls in a lavish lunch cart while a hungry mouse looks on in this atmospheric picture book inspired by the forerunner of food trucks and diners. A delectable picture book inspired by forerunners of food truck, for fans of The Night Gardener. Noses sniff the air as mouthwatering smells waft down city streets, luring growling bellies to the Night Owl. Inside this elegant, horse-drawn establishment, a feathery cook works the grill, serving up tasty dishes for shift-workers and operagoers alike: a mince pie for Fox, a ham sandwich for Badger and puddings for little Possums. Mouse, a poor street sweeper, watches as the line of customers swells, ever hopeful that someone will drop a morsel of food -- but Owl's cooking is far too delicious for more than a crumb to be found. As the evening's service winds down, weary Owl spots trembling Mouse. Has he found his own night lunch, or will he invite this small sweeper inside for a midnight feast for two? From the imagination of two acclaimed picture book creators, together for the first time, this dreamlike picture book is a magical ode to Victorian lunch wagons. Evoking the sounds, sights, smells and tastes of the city at night, Night Lunch reveals how empathy and kindness as well as dignity and gratitude can be found -- and savored -- in the most unexpected places."--